How modern technology in knowledge management can support higher educational institutions in modern learning settings - Zhao, Charles; Guetl, C.; Chang, Elizabeth (Kassel University Press, 2008)
In both academic and practically oriented literature as well as on the Internet, knowledge management is used much more frequently with respect to the business world, often in corifunction with "e-business" and "virtual organizations. It has been slow for higher education to adopt knowledge management. There is no doubt that higher education is both scholarly and operationally knowledge rich. Educational institutions are under immense pressure from governments and students to improve their effectiveness and accountability. Given the great importance in the application of knowledge management (KM) in higher education and a lot of activities in organizations, to our best knowledge there are less research and development activities in this application domain within the last few years. In this paper we want to explore how an integrated KM approach and the application ofmodern technologies are used to support higher educational institutions in modern learning settings.